Lactated Ringer’s Solution Reduces Severity, Mortality, Systemic and Local Complications in Acute Pancreatitis: A Systematic Review and Meta-Analysis - Klementina Ocskay; Péter Mátrai; Péter Hegyi; Andrea Párniczky (Biomedicines, 2023)
Fluid therapy is the cornerstone of early supportive therapy in acute pancreatitis (AP). Regrettably, the type of fluid is still debated among clinicians, despite recent evidence from randomized controlled trials (RCTs). We aimed to incorporate all evidence from RCTs comparing lactated Ringer’s solution (LR) with normal saline (NS) in adult and pediatric AP patients, with particular emphasis on clinically relevant outcomes. We evaluated RCTs comparing intravenous fluid resuscitation with LR to NS in adult or pediatric AP patients according to a prospectively registered protocol (CRD42021224542). Moderate-to-severe AP (MSAP), mortality, length of hospitalization (LoH), need for intensive care, the incidence of systemic (organ failure, OF) and local complications (in total), necrosis and pseudocyst formation were analyzed separately. Risk ratio (RR) and median difference (MD) were calculated with 95% confidence intervals (CI) using a random effect model. Risk of bias and quality of evidence were assessed. Altogether, 8 eligible RCTs were found, including 557 patients (LR: 278; NS: 279). LR reduced the risk of MSAP by 31% (RR: 0.59, 95% CI: 0.36–0.97, high quality) and the risk of death by 62% (RR: 0.48; 95% CI: 0.24–0.98, very low quality). LR was associated with a significantly lower risk of need for intensive care (RR: 0.50, 95% CI: 0.33–0.77), OF (RR: 0.78, 95% CI: 0.61–0.99) and local complications (RR: 0.64, 95% CI: 0.46–0.89). No significant risk reduction was observed for LoH (MD: −0.57 days, CI: −1.33–0.19), necrosis, pseudocyst and inflammatory parameters by LR compared to NS. LR reduces severity, mortality, need of intensive care and systemic and local complications in AP.